1996
DOI: 10.1677/joe.0.1480409
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of BRIN-BG5 and BRIN-BG7, two novel glucose-responsive insulin-secreting cell lines produced by electrofusion

Abstract: Two hybrid insulin-secreting cell lines (BRIN-BG5 and BRIN-BG7) were established by the novel approach of electrofusing RINm5F cells with New England Deaconess Hospital rat pancreatic islet cells. Cells were selected from the fusion mixture on the basis of insulin output. Wells showing five to ten times greater insulin output than parental RINm5F cells were selected, subcultured and cloned. Clonal BRIN-BG5 and BRIN-G7 cells grow as monolayers with epithelial morphology. The differences in doubling time of 28 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Another useful approach is to use electrofusion to combine the functional properties of freshly isolated islet beta‐cells with a partner cell line that can confer immortality to the beta‐cells (Table ). One such example that has lent itself to a significant number of studies is the glucose‐responsive insulin‐secreting BRIN‐BD11 cell line which, like slightly inferior clones BRIN‐BG5 and BRIN‐BG7, was produced by the electrofusion of RINm5F cells, a subclone of RIN with freshly isolated rat beta‐cells . Of these, the BRIN‐BD11 cell line in particular has shown highly desirable characteristics for a clonal beta‐cell line, having retained near‐normal beta‐cell functionality and responsiveness to glucose and other modulators of pancreatic insulin secretion .…”
Section: Development and Experimental Use Of Rodent Beta‐cell Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Another useful approach is to use electrofusion to combine the functional properties of freshly isolated islet beta‐cells with a partner cell line that can confer immortality to the beta‐cells (Table ). One such example that has lent itself to a significant number of studies is the glucose‐responsive insulin‐secreting BRIN‐BD11 cell line which, like slightly inferior clones BRIN‐BG5 and BRIN‐BG7, was produced by the electrofusion of RINm5F cells, a subclone of RIN with freshly isolated rat beta‐cells . Of these, the BRIN‐BD11 cell line in particular has shown highly desirable characteristics for a clonal beta‐cell line, having retained near‐normal beta‐cell functionality and responsiveness to glucose and other modulators of pancreatic insulin secretion .…”
Section: Development and Experimental Use Of Rodent Beta‐cell Linesmentioning
confidence: 99%
“…Following previous success with the use of electrofusion technology to create the BRIN‐BD11 and related rat beta‐cell lines (Table ), similar technology has been applied to immortalize human pancreatic beta‐cells. Three electrofusion‐derived human beta‐cell lines have been described in literature by McCluskey et al, namely 1.1B4, 1.1E7 and 1.4E7 (Table ).…”
Section: Human Beta‐cell Line Development and Potential For Therapeutmentioning
confidence: 99%
“…Electrofusion of normal pancreatic b cells with RINm5F cells might be expected to yield hybrid cells which obtain immortality from the established cell line and appropriate features of insulin synthesis and secretion from the normal b cells. Using this approach with selection of immortal hybrids on the basis of high insulin output, three novel clonal pancreatic b cell lines were established and designated BRIN-BG5, BRIN-BG7 and BRIN-BD11 ( [74,75]; table 1). Primary characterization studies revealed that each clone shows subtle morphological differences coupled with different patterns and magnitudes of responsiveness to glucose and other key regulators of b cell function [74,75].…”
Section: Generation Of Glucose-responsive B Cell Lines By Electrofusionmentioning
confidence: 99%
“…Using this approach with selection of immortal hybrids on the basis of high insulin output, three novel clonal pancreatic β cell lines were established and designated BRIN‐BG5, BRIN‐BG7 and BRIN‐BD11 (74,75]; Table 1). Primary characterization studies revealed that each clone shows subtle morphological differences coupled with different patterns and magnitudes of responsiveness to glucose and other key regulators of β cell function[74, 75]. Of these, BRIN‐BD11 cells most closely mirror the characteristics of the parental β cell.…”
Section: Generation Of Glucose‐responsive β Cell Lines By Electrofusionmentioning
confidence: 99%
“…As such, electrofusion‐derived hybrid cells should obtain immortality from the RINm5F fusion partner and intact features of insulin biosynthesis and secretion from the normal parental pancreatic β‐cells. Adopting this novel approach, three clonal rodent cell lines were established following electrofusion of New England Deaconess hospital (NEDH) rat β‐cells with immortal RINm5F cells, originally derived from the transplantable NEDH rat insulinoma (McClenaghan et al 1996 a , c ). Procedures adopted for the isolation of these three clonal β‐cells (denoted BRIN‐BD11, BRIN‐BG5 and BRIN‐BG7) are described in detail elsewhere (McClenaghan et al 1996 a , c ), but the BRIN nomenclature comes from the B‐cell‐RIN cell fusion, with each cell line cloned from well B into three wells: D11, G5 and G7.…”
mentioning
confidence: 99%